Untold History: Supreme Council Foreign Affairs Commission (Main Aspects of Activity) (Parliamentary Studies, 2021)
20 March 1990 saw the establishment of the Supreme Council Foreign Affairs Commission, which operated until 11 November 1992. It contained 18 members, and its first President was Emanuelis Zingeris. The Commission’s main goal was inter-parliamentary relations, recognition of Lithuania’s statehood and its return to the international community. The first year of the independence was particularly difficult since there was a lack of international relations, finances and diplomatic experience. With the help of expatriate Lithuanians as well as by establishing formal and informal contacts and offices, which were turned into embassies later on, the commissioners argued that Lithuania must become part of international politics. It was Lithuania’s “Wild West of diplomacy”
Keywords: Supreme Council; Foreign Affairs Commission; independence; recognition; diplomacy